Problem Based Learning dan Discovery Learning Sebagai Prediktor Berpikir Kreatif - Martina Dewi Lengo; Jolis Joskar Anderias Djami (Universitas Kanjuruhan Malang, 2019)
This research aims to investigate the influence of problem-based learning on creative thinking, the influence of discovery learning to creative thinking, and the simultaneous influence of problem-based learning and discovery learning to creative thinking. This research is explanatory with the processing and discussion of data using quantitative analysis technique. This research will be conducted at SMA Negeri 1 Rote Barat Daya, which is located in Oetefu Hamlet, Rote Barat Daya District, Rote Ndao Regency, East Nusa Tenggara province. The respondents involved in this study amounted to 88 high school students. The questionnaire used was adapted from a problem-based learning environment, inventory discovery of learning, and Torrance test of Creative Thinking (TTCT). The results showed that problem-based learning has no significant influence on creative thinking, discovery Learning has a positive and significant influence on creative thinking, and simultaneous testing of problem-based learning and discovery learning has no significant influence on the creative thinking of SMA Negeri 1 Rote Barat Daya.